ANALYSIS OF WATER DISTRIBUTION SERVICES BY PERUMDAM TIRTA KHATULISTIWA IN PONTIANAK BARAT SUB-DISTRICT USING EPANET - Pratama, Andikha; Yulianto, Eko; Gunarto, Danang; Soeryamassoeka, S B (Fakultas Teknik Universitas Tanjungpura, 2022)
PERUMDA Air Minum Tirta Khatulistiwa distributes clean water in Pontianak Barat District. Services are divided into several zones, one of which is zone H which includes Pal Lima Village and Sungai Beliung Village. only 63.82% of the population is served with a pumping capacity of 100 liters/second, based on this data, the service in zone H is not optimal. Population growth results in a lack of clean water in zone H at peak hours, so it is necessary to analyze water needs for existing conditions and conditions for the next 20 years. Population projection using Arithmetic, Geometric and Least Square methods. Analysis of water demand in zone H is calculated for domestic and non-domestic water, distribution network analysis is carried out using the Epanet program. Network analysis is simulated into 5 conditions. The results of the study found that the demand for clean water for the existing served population was 63.82% at 110.20 liters/second and the existing condition for the served population was 90% at 145.78 liters/second, while the need for clean water in the next 20 years was 341.43. liters/second. Short-term improvements that can be made are to increase the exsisting pumping capacity to 200 liters/second, while the long-term improvements are to increase the exsisting pumping capacity to 400 liters/second and pump head to 40 m, adding a booster in zone H with a pumping capacity of 200 liters. /second and pump head 30 m